Geopolitik dan geostrategi: Kebijakan strategis dan keamanan nasional dalam hubungan internasional - rahmadina, dwi aurora nayla (Maliki Interdisciplinary Journal, 2026)
The study of geopolitics and geostrategy is crucial in understanding the dynamics of interstate relations and their implications for national security and development. This research aims to examine geopolitics as a conceptual foundation for shaping strategic policies and to analyze geostrategy as a practical instrument for addressing global challenges. The method employed is a literature review with a descriptive qualitative approach, focusing on a comprehensive analysis of theories and practices related to geopolitics and geostrategy. The findings reveal that the integration of geopolitics and geostrategy provides an effective framework for states to formulate foreign policy, strengthen bargaining positions, and maintain national stability amid global transformations.These results affirm that the Crusades represent a multidimensional phenomenon reflecting the complexity of the relationship between religion and politics in history.